Kegagalan Referendum Konstitusi Eropa: "Quo Vadis" Uni Eropa? - Hutabarat, Leonard (Global: Jurnal Politik Internasional, 2005)
A geopolitical revolution of historic force is under way across the Atlantic: the unification of Europe. This new "United States of Europe" has more people, more trade, more wealth, and more votes every international body. Europe's new constitution even establishes an official European Unimotto: "United in Diversity". This article will discuss why European vote "no" to the Europe Constitutional Treaty in last May in France as one of the founding fathers of the union. What would be the consequences of French's rejection of the Treaty. Would a "no" vote signal the end of tEuropean integration project? Would a vote against the Constitution be a vote against free-market economics? The article also explains what will be the next possible scenarios and outcomes for "the European dream". Where the European Union go from here?